Assessment of Hemodialysis Patients’ knowledge Concerning Uremic Pruritus - Al-Khafaji, Marwan Sawood Rabea; Al-Mayahi, Ayad (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): This study aims to assess the knowledge of hemodialysis patients about uremic pruritus and to determine whether there is a relationship between the demographic and clinical characteristics of hemodialysis patients with their level of knowledge about uremic pruritus. Method: A descriptive study was conducted to assess the knowledge of hemodialysis patients about uremic pruritus. The study was conducted at the Al-Hussein Center for hemodialysis at Al-Hussein Teaching Hospital in Thi-Qar Governorate, for the period from 29th December, 2022 to 29th April, 2023. A non-probability purposive sample of 30 patients was selected from hemodialysis patients, their ages ranged from 20 to 70 years. The research tool consisted of three parts. The first part consisted of demographic information, the second part consisted of clinical information of the hemodialysis patients, and the third part consisted of a questionnaire to assess the knowledge of hemodialysis patients about uremic pruritus (including items and domains). Results: The results of the study showed that the knowledge of hemodialysis patients about uremic pruritus was at a weak and their knowledge was not affected by their demographic and clinical characteristics. Conclusion: This study concluded the hemodialysis patients has a poor level and little of knowledge about uremic pruritus. Recommendations: Educational courses should be established to manage uremic pruritus, and the hemodialysis patients should be motivated to participate in health education programs for the purpose of increasing their knowledge and information about uremic pruritus.